Analysis of factors influencing changes in medical behavior under the context of DRG payment method reform: a structural equation modeling approach - Jiang, Chen; Qin, Dawei; Zhang, JinPeng; Guan, Yanpeng; Li, Fengming; Jiang, Liangmei (Frontiers in Public Health, 2025)
ObjectivesThis study aims to assess the understanding of policies, cognitive awareness, and medical behavior patterns among healthcare workers about the reform of the diagnosis-related group (DRG) payment method. A questionnaire survey was conducted to examine how policy comprehension and cognition influence changes in medical behavior, targeting medical personnel in a northern Chinese city.MethodsAn online survey was administered from November to December 2023, covering primary, secondary, and tertiary medical institutions in a city that had implemented DRG payments. The survey gathered demographic data and information on policy comprehension, medical behavior patterns, and policy cognition. Structural equation modeling was employed to analyze the relationships among these factors and their impact on shifts in medical behavior.ResultsThe findings revealed that policy comprehension did not significantly affect policy cognition. Nonetheless, a higher level of policy comprehension was linked to a negative influence on positive medical behavior (t = −0.115, p < 0.05), and a positive impact on negative medical behavior (t = 3.746, p < 0.001). Conversely, positive policy cognition was found to promote positive medical behavior (t = 10.756, p < 0.001), while negative policy cognition was associated with an increase in negative behavior (t = 12.282, p < 0.001).ConclusionBehavioral adaptations to DRG reform are driven primarily by cognitive evaluations (positive/negative policy perceptions), not mere policy knowledge. Contrary to expectations, deeper policy understanding correlates with increased negative medical behavior and reduced positive behavior, suggesting that technical training alone may inadvertently incentivize gaming under financial pressures. Positive cognition strongly promotes desirable behaviors, while negative cognition exacerbates detrimental practices. To optimize reform success, China must prioritize value-oriented training (emphasizing DRG’s systemic goals over mechanics) and implement intelligent auditing mechanisms to curb high-risk behaviors during transition.